Accounting System Analysis of School Operational Assistance Fund Management (Bos) at SMA XYZ at Jonggol - Yusuf Harbi (Peneliti.net, 2022)
This study aims to understand how the BOS fund management system at SMA XYZ Jonggol. The object of this research is SMA XYZ Jonggol which is located in Jonggol, Bogor Regency. This study uses a descriptive qualitative method by using the interview, observation and documentation process to provide a complete picture and describe the facts encountered in the field. The results showed that the management and management system carried out at XYZ High School was quite good and adequate in accordance with the existing National Education Standards and Technical Guidelines for BOS.